Mobile phone use among Manipuri youth during Covid-19 lockdown - Dr. Achom Roshan Kumar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The imposition of Covid-19 lockdown for months during the first half of 2020 brought about manifold increase in the use of mobile/smartphone among youths in Manipur. The complete lockdown for a long period of time brought about certain new ways of using mobile phone. This period saw the advent of online class in schools, colleges and educational institutions throughout the state. The sudden increase of mobile phone use for various purposes from communicating with one’s friends and relatives to online purchases, social networking, mobile gaming, online business etc is simply unprecedented. The present paper aims to unfold the various ways in which mobile/ smartphone is used by youths during Covid-19 lockdown. Incremental use of smartphone in the number of hours, mobile gaming, social media, virtual class and online shopping has been found in this study. The youths who are at the forefront of this digital communication revolution should be provided careful and proper guidance so that they may not get lost in the midst of this ever-evolving digital jungle.